2011
DOI: 10.1097/igc.0b013e31822d2abd
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 Induces Up-Regulation of Chemokine and Cytokine Expression Via Activation of the Nuclear Factor κB and Extracellular Signal–Regulated Kinase 1/2 Pathways in Gynecologic Cancer Cell Lines

Abstract: These results demonstrated that IL-17 may regulate chemokines and cytokines in gynecologic cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In Myc-CaP/CR cells, neither U0126 nor PDTC inhibited IL-17A-induced COX-2 protein expression (data not shown). These findings suggest that IL-17 indeed acts through NF-κB and ERK1/2 signaling pathways in A549 and HeLa cells to regulate expression of downstream genes, which is consistent with our previous study [11]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In Myc-CaP/CR cells, neither U0126 nor PDTC inhibited IL-17A-induced COX-2 protein expression (data not shown). These findings suggest that IL-17 indeed acts through NF-κB and ERK1/2 signaling pathways in A549 and HeLa cells to regulate expression of downstream genes, which is consistent with our previous study [11]. …”
Section: Resultssupporting
confidence: 93%
“…We have previously shown that IL-17 up-regulates expression of chemokines and cytokines in human cancer cell lines such as HeLa, HEC-1-B, and SKOV3 [11]. In this study, we found that IL-17 significantly up-regulated COX-2 mRNA expression in HeLa, A549, and Myc-CaP/CR cancer cell lines (p < 0.05) (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Previous studies did not find an effect of IL-17 on HeLa and IC1 cervical cancer cell growth. 33,34 These results suggest that IL-17 may increase cellular tightness in cervical cancer cells. Additionally, both a high number of IL-17…”
Section: Discussionmentioning
confidence: 75%
“…As shown in Figure 5A, miR-23b expression was decreased in IL-17A-treated cells at 3 and 6 h and returned to baseline at 24 h. NF-κB was a crucial target of IL-17A signaling pathway in many types of cells [3133] and it had been reported to function as a tumor promoter in inflammation-associated cancer [34]. Western blot analysis showed that IL-17A increased the protein level of p65 in the nuclear fraction and decreased it in the cytosolic fraction (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%